Breaking stereotypes, building inclusion: blind hiring strategies as catalysts for a diverse and discrimination-free workplace - Vivek, R.; Krupskyi, O. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2024)
This article explores blind hiring strategies as an effective tool for enhancing diversity and inclusion in modern workplaces. It delves into the conceptual foundations, practical implementations, and real-world case studies that reveal the potential of blind hiring in mitigating unconscious biases. The key findings highlight the benefits of this approach, such as increased fairness, improved organizational reputation, and overall success. Simultaneously, the challenges associated with implementing this strategy are analyzed, and actionable steps to overcome them are proposed. The research demonstrates that blind hiring can serve as a cornerstone in building diverse and inclusive cultures in contemporary organizations. The article underscores the need for a holistic perspective that transcends recruitment to include overall organizational practices and culture. Best practices for blind hiring, coupled with successful application examples, provide a roadmap for organizations aspiring to leverage the benefits of a diverse and inclusive workforce. The importance of continuous evaluation and feedback on the blind hiring process to ensure alignment with diversity and inclusion goals is emphasized. Additionally, the study advocates for raising awareness among recruiters, hiring managers, and stakeholders to foster an inclusive mindset throughout the organization, creating an ideal environment for blind hiring to thrive. Given the increasingly interconnected and diverse global workforce, fair hiring practices are more critical than ever. Blind hiring is positioned as a robust mechanism to achieve these objectives, leading to a more innovative workforce, greater employee satisfaction, and enhanced corporate reputation. Hence, blind hiring represents a significant step towards redressing historical inequities and advancing organizations into a future of equality, diversity, and inclusion. This ensures alignment with organizational goals and fosters long-term success in modern competitive environments.